(3cJGH JKbja GdJYQja HGdeUWdM GdTQjas - (3TgGH GdOjf CHj GdYHGS CMeO Hf aVd Gddg GdYeQjs ((3MeRI Hf bGSe Hf GdTgGHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ejR ebGOjQ GdQJH hHYO adeG GdJeG hWHY cd Qbjb GdTeGFd Ydi QO GdCOH GdMeGe s
(3BNQgG (B:s
(3ai GdCd hbO YH YHGHg hYi SQGHg hWHb CWHGb GdZeGe hGfJTQ EfJTGQ GdXdGe ai GdYde ehbY GdfbO dOjge dYdege EPG cSO YfOge Cf dg bhekG jJab Ydjge hGddg jhabfG deG gh GUdM hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3hgj faS fSNI GdJYQjas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdMOjK h GdeUWdMs